Health care costs and financing in world perspective. - Roemer, M. I. (Yale Journal of Biology and Medicine, 1991)
Expenditures for health services, as a percentage of national wealth (gross national product, or GNP), have been rising throughout the world. Data to quantify this trend are available for many industrialized countries. The share of health spending derived from governmental sources has also been increasing. Mandatory or social insurance has developed to support health services in 70 nations. While widely used for paying doctors on a fee basis or by capitation, in Latin America doctors are organized in polyclinics and paid by salaries. General revenues are used to support Ministry of Health programs. Among health expenditures, the largest share goes to hospitalization. Cost sharing by patients is widely used to control rising costs. World trends have promoted equity in health care delivery.